Meta-analysis of interventions to reduce door to needle times in acute ischaemic stroke patients. Issue 3 (3rd August 2020) - Siarkowski, Michael; Lin, Katie; Li, Shari S; Al Sultan, Abdulaziz; Ganshorn, Heather; Kamal, Noreen; Hill, Michael; Lang, Eddy
Abstract : Background: Door-to-needle time (DTN) has an important impact on thrombolysis and reperfusion outcomes in the treatment of acute ischaemic stroke. This systematic review is a critical synthesis of studies evaluating DTN reduction strategies. Method: Ovid MEDLINE, PubMed, Cochrane Database of Systematic Reviews, CINAHL, ProQuest dissertations and LILACS were used as bibliographic databases for primary literature. CIHI, Health Quality Council of Alberta, Health Quality Ontario and websites of heart and stroke associations in Canada, USA, UK, Australia and New Zealand were used as sources of grey literature. Searched reports were screened by title and abstract, and full texts were located for review. Articles quality was evaluated using National Institute of Health's Study Quality Assessment tools. Methods for improving DTN were categorised under 13 DTN reduction strategies, primarily adapted from the Target: Stroke Phase II recommendations, and including two additional categories: Strategies not encompassed by any Target: Stroke recommendation, and Combinations of Interventions. Results: 96 studies (4 randomised control trials, 1 review, 91 observational pre/post studies) were included in the review. All strategies and interventions resulted in a reduction of DTN. Approaches using combinations of interventions were the most effective at reducing DTN (33.77% DTN reduction, standard mean difference=1.857, 95% CI=1.510–2.205), and were more effective than approaches using only a single strategy (p=0.040). DTN reduction was associated with the duration of the DTN reduction programme at each facility (p=0.006). Interpretation: The greatest reductions in DTN were observed when implementing combinations of DTN reduction strategies, although there was no significant advantage to implementing more than two strategies simultaneously. PROSPERO registration number: 42016036215.